Suspicion, screening, and diagnosis of wild‐type transthyretin amyloid cardiomyopathy: a systematic literature review - Katrine Bay; Finn Gustafsson; Michael Maiborg; Anne Bagger‐Bahnsen; Anne Mette Strand; Trine Pilgaard; Steen Hvitfeldt Poulsen (ESC Heart Failure)
Abstract Wild‐type transthyretin amyloid cardiomyopathy (ATTRwt CM) is a more common disease than previously thought. Awareness of ATTRwt CM and its diagnosis has been challenged by its unspecific and widely distributed clinical manifestations and traditionally invasive diagnostic tools. Recent advances in echocardiography and cardiac magnetic resonance (CMR), non‐invasive diagnosis by bone scintigraphy, and the development of disease‐modifying treatments have resulted in an increased interest, reflected in multiple publications especially during the last decade. To get an overview of the scientific knowledge and gaps related to patient entry, suspicion, diagnosis, and systematic screening of ATTRwt CM, we developed a framework to systematically map the available evidence of (i) when to suspect ATTRwt CM in a patient, (ii) how to diagnose the disease, and (iii) which at‐risk populations to screen for ATTRwt CM. Articles published between 2010 and August 2021 containing part of or a full diagnostic pathway for ATTRwt CM were included. From these articles, data for patient entry, suspicion, diagnosis, and screening were extracted, as were key study design and results from the original studies referred to. A total of 50 articles met the inclusion criteria. Of these, five were position statements from academic societies, while one was a clinical guideline. Three articles discussed the importance of primary care providers in terms of patient entry, while the remaining articles had the cardiovascular setting as point of departure. The most frequently mentioned suspicion criteria were ventricular wall thickening (44/50), carpal tunnel syndrome (42/50), and late gadolinium enhancement on CMR (43/50). Diagnostic pathways varied slightly, but most included bone scintigraphy, exclusion of light‐chain amyloidosis, and the possibility of doing a biopsy. Systematic screening was mentioned in 16 articles, 10 of which suggested specific at‐risk populations for screening. The European Society of Cardiology recommends to screen patients with a wall thickness ≥12 mm and heart failure, aortic stenosis, or red flag symptoms, especially if they are >65 years. The underlying evidence was generally good for diagnosis, while significant gaps were identified for the relevance and mutual ranking of the different suspicion criteria and for systematic screening. Conclusively, patient entry was neglected in the reviewed literature. While multiple red flags were described, high‐quality prospective studies designed to evaluate their suitability as suspicion criteria were lacking. An upcoming task lies in defining and evaluating at‐risk populations for screening. All are steps needed to promote early detection and diagnosis of ATTRwt CM, a prerequisite for timely treatment.